Association between parental psychiatric disorders and risk of offspring autism spectrum disorder: a Swedish and Finnish population-based cohort studyResearch in context - Weiyao Yin; Anna Pulakka; Abraham Reichenberg; Alexander Kolevzon; Jonas F. Ludvigsson; Kari Risnes; Marius Lahti-Pulkkinen; Martina Persson; Michael E. Silverman; Ulrika Åden; Eero Kajantie; Sven Sandin (Elsevier, 2024)
Summary: Background: Roughly more than one in six adults worldwide suffer from psychiatric conditions. Sporadic studies have associated parental psychiatric disorders with autism spectrum disorder in offspring. Comprehensively examining the association between parental psychiatric disorders and offspring autism spectrum disorder is needed to guide health policies, and to inform etiologic studies. Methods: We included all children born in Sweden and Finland 1997-2016. Diagnoses were clinically ascertained from National Registers through 2017. We calculated adjusted hazard ratios (aHRs) and 95% confidence intervals (CIs) for autism spectrum disorder in offspring of fathers and mothers with psychiatric disorders, in both parents jointly and across co-occurring conditions. Findings: Among 2,505,842 children, 33,612 were diagnosed with autism spectrum disorder, of which 20% had a parent with psychiatric disorders. The risk of autism spectrum disorder was increased across all psychiatric disorders in fathers (Sweden: aHR = 2.02, 95% CI = 1.92-2.12; Finland: aHR = 1.63, 95% CI = 1.50-1.77), mothers (Sweden: aHR = 2.34, 95% CI = 2.24-2.43; Finland aHR = 2.12, 95% CI = 1.92-2.28), or both parents (Sweden: aHR = 3.76, 95% CI = 3.48-4.07; Finland aHR = 3.61, 95% CI = 3.20-4.07), compared to neither parents. Co-occurrence of parental psychiatric disorders further increased risk (e.g., Sweden: for one, two or ≥three different diagnostic categories compared to no diagnosis, in fathers aHR = 1.81, 2.07, 2.52; in mothers aHR = 2.05, 2.63, 3.57). Interpretation: Psychiatric disorders in both parents conveyed the highest risk of offspring autism spectrum disorder, followed by mothers and then fathers. The risk increased with number of co-occurring disorders. All parental psychiatric disorders were associated with increased the risk of autism spectrum disorder. To reliably assess the risk of autism spectrum disorder in children, a comprehensive history incorporating the full range of parental psychiatric disorders is needed beyond solely focusing on familial autism spectrum disorder. Funding: Swedish-Research-Council-2021-0214.